Pemberdayaan Masyarakat Melalui Hukum dan HAM dengan Sosialisasi Terkait Hak Perempuan dan Anak - Paskalia Priti Tokan; Rita Ririn Duwijayanti; Capah Veronika Ester; Muhammad Ammar J (Jurnal Pengabdian Masyarakat Waradin, 2025)
Field Study and Community Service carried out by Group 22, themed "Law-Aware Society," aims to increase legal awareness and understanding of citizens' rights in selected locations. This program encompasses community empowerment through Law and Human Rights, socialization of legal awareness, and socialization regarding children's and women's rights. The implementation of this program showed active participation from the community and created a positive synergy between students, residents, and related stakeholders. Despite challenges such as the initial lack of community awareness, the program successfully delivered significant positive impacts. Indicators of the program's success include increased community participation and understanding of their rights and obligations. These results demonstrate that community service can be an effective means of empowering communities and instilling values of legal and human rights awareness. To enhance effectiveness and impact in the future, it is recommended to map community needs, develop measurable success indicators, increase interaction with the community, integrate the program with other empowerment activities, and implement systematic evaluation mechanisms. Thus, KKN activities can provide greater and more sustainable benefits to the community while enhancing the quality of students' learning experiences in community service.